2006
DOI: 10.1157/13084222
|View full text |Cite
|
Sign up to set email alerts
|

Latex allergy in children: a follow-up study

Abstract: Strict compliance with latex avoidance instructions is essential both inside and outside the hospital. Greater emphasis should be placed on reducing latex exposure in the home and school environments, as such contact could maintain positive IgE-antibody levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Only few follow-up studies focusing on small samples of allergic patients have been conducted to determine the long-term outcome outside the hospital setting but some of them were able to highlight the possible benefits of latex avoidance. In a 2006 investigation (with a median followup of 3 years) Die ´guez Pastor et al [53] showed that specific-IgE to latex were higher in patients who had contact with latex compared with those who completely avoided it, and a recent study conducted by Dhonncha et al [55] showed that a proportion of patients who managed to avoid latex for a period of time (median follow-up of 16 years) no longer showed clinical signs of latex allergy. Further larger studies are certainly needed to determine the prognostic significance of latex avoidance.…”
Section: The Struggle For Latex Avoidance Outside the Healthcare Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Only few follow-up studies focusing on small samples of allergic patients have been conducted to determine the long-term outcome outside the hospital setting but some of them were able to highlight the possible benefits of latex avoidance. In a 2006 investigation (with a median followup of 3 years) Die ´guez Pastor et al [53] showed that specific-IgE to latex were higher in patients who had contact with latex compared with those who completely avoided it, and a recent study conducted by Dhonncha et al [55] showed that a proportion of patients who managed to avoid latex for a period of time (median follow-up of 16 years) no longer showed clinical signs of latex allergy. Further larger studies are certainly needed to determine the prognostic significance of latex avoidance.…”
Section: The Struggle For Latex Avoidance Outside the Healthcare Settingmentioning
confidence: 99%
“…Overall, latex exposure remains a persistent risk for allergic patients, and many studies have showed practical difficulties for them to translate latex avoidance into action even after being thoroughly advised [51][52][53][54]. Only few follow-up studies focusing on small samples of allergic patients have been conducted to determine the long-term outcome outside the hospital setting but some of them were able to highlight the possible benefits of latex avoidance.…”
Section: The Struggle For Latex Avoidance Outside the Healthcare Settingmentioning
confidence: 99%